2021
DOI: 10.1007/s10548-020-00816-y
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Nociceptive Processing: Effect of Intra-Epidermal Electric Stimulus Properties on Detection Probability and Evoked Potentials

Abstract: Monitoring nociceptive processing is a current challenge due to a lack of objective measures. Recently, we developed a method for simultaneous tracking of psychophysical detection probability and brain evoked potentials in response to intra-epidermal stimulation. An exploratory investigation showed that we could quantify nociceptive system behavior by estimating the effect of stimulus properties on the evoked potential (EP). The goal in this work was to accurately measure nociceptive system behavior using this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
5
15
0
Order By: Relevance
“…Frequency analysis showed significant peaks at stimulation frequencies (3–7 Hz), but did not find any significant harmonic or intermodulation frequencies that would confirm nonlinearity of nociceptive processing. Using the phase delay of significant nociceptive SSEPs at 3–7 Hz stimulation, we showed that there was an average time delay for both frequencies on the contralateral central midline electrodes (C5, C3, C1 and Cz) of 168 ms which is similar to the average delay of the N1 (160 ms) in previous studies measuring evoked potentials to single intra-epidermal pulses (van den Berg and Buitenweg 2021 ; van den Berg et al 2020 ), suggesting that the nociceptive SSEP might result from the activation of similar neural pathways.…”
Section: Introductionsupporting
confidence: 77%
“…Frequency analysis showed significant peaks at stimulation frequencies (3–7 Hz), but did not find any significant harmonic or intermodulation frequencies that would confirm nonlinearity of nociceptive processing. Using the phase delay of significant nociceptive SSEPs at 3–7 Hz stimulation, we showed that there was an average time delay for both frequencies on the contralateral central midline electrodes (C5, C3, C1 and Cz) of 168 ms which is similar to the average delay of the N1 (160 ms) in previous studies measuring evoked potentials to single intra-epidermal pulses (van den Berg and Buitenweg 2021 ; van den Berg et al 2020 ), suggesting that the nociceptive SSEP might result from the activation of similar neural pathways.…”
Section: Introductionsupporting
confidence: 77%
“…In this work, we extracted individual psychophysical and EEG features of FBSS patients and healthy controls to study whether a combination of these features could aid the observation of altered nociceptive processing in chronic pain patients. Note that the influence of the experimental procedure parameters on outcomes has been discussed previously by Van den Berg & Buitenweg [8], and is therefore not studied here.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, effects of the same stimulus properties on the detection probability can be quantified using generalized linear (mixed) models. A recent study [8] used this method to show that the various steps of processing a nociceptive stimulus, including peripheral nerve fiber recruitment, central synaptic summation, and habituation to a repeated stimulus are reflected by these effects of stimulus properties on detection probability and the evoked potential.…”
Section: Introductionmentioning
confidence: 99%
“…Eye blinks and muscular activity were removed from the EEG by independent component analysis. EP signals were derived from the CPz-A1A2 derivation, which was in line with the previous studies [8,9]. From this derivation, a grand average EP and the P2 latency were computed.…”
Section: Evoked Potentialsmentioning
confidence: 92%
“…Using the NDT-EP method, we have shown that several nociceptive processing steps, including peripheral nerve fiber recruitment, central synaptic summation, and habituation to repetitive administered trials, can be quantified in healthy subjects [8]. Also, we have demonstrated that these results can be replicated in a clinical environment and that it is sensitive to observe phenomena of altered central nociceptive processing in chronic pain patients, such as failed back surgery syndrome [9].…”
Section: Introductionmentioning
confidence: 99%